RESPON PEMANFAATAN PUPUK ORGANIK IKAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KUBIS - Bina Beru Karo; Agustina E Marpaung; Susilawati Barus (Universitas Quality, 2018)
Fish organic fertilizer has a high nutrient content for plants. Giving organic fish fertilizer to cabbage can increase the growth and production of cabbage. This study aims to determine the way and the right dose of organic fish fertilizer in cabbage plants. This research was conducted at Berastagi experimental farm which began in June - September 2018. The experimental design used was a Randomized Block Design factorial with 3 replications, where the first factor is the type of Fish organic fertilizer (I1. Dry and I2. Fermentation). The second factor is the dose of fish organic fertilizer (D0. 0, D1. 300 kg / ha, D2. 600 kg / ha, D3. 900 kg / ha and D4. 1200 kg / ha). The results showed that the fish organic fertilizer with types dried and fermented were not different significant in increasing the growth and production of cabbage plants. The dose of fish organic fertilizer can increase the growth and production of cabbage plants. Giving 1,200 kh / ha of fish fertilizer yields the highest diameter of crop, crop weight and production, ie 14.83 cm, 0.64 kg and 30.36 kg / 5 m2. There is no interaction between type and dose of fish organic fertilizer on the growth and production of cabbage plants.